Development of Capacity and Level-of-Service for Uninterrupted Exclusive Motorcycle Lanes in Malaysia - Hamid, Hussain (2006)
In developing ASEAN countries, the key road accident problems arise from the high proportion of motorcycles in the mixed vehicle population. Considering that motorcycles are popular mode of personal travel and that they are highly numbered on the roads, the provision of exclusive motorcycle lanes is expected to reduce accidents and improve motorcycle safety. Studies have proven that segregation is the best engineering practice to save lives of motorcyclists. Acknowledging these benefits, the Malaysian government has adopted a policy to provide exclusive motorcycle facilities along its new highways and federal roads. The need to provide this special facility has brought to light the deficiencies in studies related on motorcycle traffic sciences, operations and facility design. This research initially attempts to establish the characteristics of key components of a motorcycle-traffic system in Malaysia, i.e. the motorcyclerider unit, motorcyclist space requirement and riding manner along motorcycle lane of various lane widths. Then, it seeks to establish the fundamental motorcycle speed-flow-density relationships along uninterrupted motorcycle lanes in Malaysia. This would enable the maximum motorcycle flow, critical speed and critical density at capacity conditions to be estimated. Finally the level-of-service criteria for an exclusive motorcycle lane facility would be developed, thus allowing the motorcycle design charts and tables to be produced. To understand the key components of a motorcycle-traffic system, digital recordings of motorcyclists along the existing motorcycle lanes in Malaysia were captured. Basic dimensions of a motorcycle/rider unit were directly measured. The separation distance between side-by-side motorcyclists was obtained by employing the digital recording technique. The motorcyclist operating space was then established. Three-stages of field and experimental studies was conducted to observe the motorcyclists riding manner along various lane widths from low to high volume conditions. To establish the fundamental motorcycle speed-flow-density relationships and to develop the level-of-service criteria, the aggregated data from 8 sites ranging from the stable flow to unstable conditions were plotted. A simple linear regression analysis was conducted on the motorcycle speed on motorcycle density function to obtain the best linear regression equation that describes the relationship. Once the motorcycle speed-density relationship was established, the motorcycle speed-flow and motorcycle flow-density relationships were derived. The demarcation of the level-of service boundaries for the uninterrupted exclusive motorcycle lanes was guided by the volume-capacity ratio (v/c) and service flow rates. Results of the research revealed that the small- and medium-sized type motorcycles (150 c.c. and below) are the commonly used type in Malaysia. A single static motorcyclist spans about 0.8 m wide, but requires a mean width of 1.3 m to operate. In a lane width of 1.7 m or below, motorcycle flow applies the lane or headway concept. While in lanes of width between 1.7 m and 3.4 m, the motorcycle flow adopts the space concept. This highlights that 1.7 m is the optimum lane width where motorcyclists would travel in a single file, even during low speeds and high motorcycle flow conditions. There is not enough space for faster motorcyclists to pass the slower ones within the 1.7 m motorcycle lanes. In the headway concept (W ≤ 1.7 m), capacity is reached at a maximum motorcycle flow of 3306 mc/hr/lane, corresponding to a critical speed of 13 km/hr and critical density of 235 mc/km/lane. As for the space concept (1.7 m < W ≤ 3.4 m), capacity occurs at a maximum motorcycle flow of 2207 mc/hr/m. This corresponds to a critical motorcycle speed of 13 km/hr and critical motorcycle density of 0.166 mc/m2 (or space of 6.0 m2/mc). Based on the speed-flow-density relationships and the volume-capacity ratio, the level-of-service boundaries were demarcated. Subsequently, tables and charts of maximum motorcycle flow rates related to level-ofservices for different motorcycle lane widths were developed. The outcome provides useful input in developing design guidelines for motorcycle facilities in countries with high number of motorcycles in the effort to curb motorcycle safety problems. This study is seen as an initial effort to fill the missing link in basic research of motorcycle traffic sciences, operations and facility design that existed among various land transportation facilities, thus contributing new knowledge to the field of transportation engineering.